What determines pension insurance participation in China?: triangulation and the intertwined relationship among employers, employees and the government - Guo, Yu; Tian, Mo; Han, Keqing; Johnson, Karl; Zhao, Liqiu (Taylor and Francis, 2016)
The current study draws on the Advocacy Coalition Framework to examine what determines employees’ pension participation in China. For the purpose of exploring which employees actually receive pension coverage and why, econometric analysis was conducted with China’s Employer–Employee Matched Survey data (N = 3412). A variety of both individual factors, ranging from age and Hukou status to job characteristics, and macro factors, including interprovincial migration and level of economic development, are all found to predict insurance coverage. Qualitative research results contextualize these findings by discussing the often ambivalent and triangulated relations among employers, employees and government. These three groups primarily use shared core policy beliefs to structure their interactions in the form of advocacy coalitions. Various types of cross-coalition interaction, including negotiation, cooperation and conflict, are examined. These findings carry both theoretical and policy implications.